PENGETAHUAN, PERSEPSI DAN SIKAP PENGURUS MASJID TERHADAP PERBANKAN SYARIAH - Isa, Muhammad (JURNAL EKONOMI DAN BISNIS ISLAM, 2018)
This study aims to identify and describe the knowledge, perceptions and attitudes of mosque administrators in Panyabungan Barat District, Mandailing Natal District about Islamic Banking. This research was conducted with qualitative methods. Data collection for this study uses interview, observation and documentation techniques. The research subjects were administrators of mosques in the West Panyabungan District. Data analysis was aided by Focused Group Discussion (FGD) activities. From this study, it was concluded that in general the mosque administrators in Panyabungan Barat District already knew that Islamic banks were free of usury but they did not yet know the products and services in Islamic banks in more detail. Managers of mosques in Panyabungan Barat District have a positive perception of Islamic banking and a Muslim should prioritize Islamic banking products and services. But they also continue to tolerate the use of products and services of conventional banks in a forced state. Furthermore, their knowledge of Islamic banks and positive perceptions about Islamic banks did not really support their attitude in daily life to utilize Islamic banking products and services. In fact they are still interested in using conventional banks if the service is better.